Pengaruh Produk Domestik Regional Bruto, Tingkat Pendidikan dan Kesehatan Terhadap Penyerapan Tenaga Kerja di Indonesia Tahun 2017-2023 - Silvie Putri Wahyu Efendi; Ruth Eviana Hutabarat (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the impact of GRDP, education level, and health on employment in Indonesia during the period 2017-2023. A quantitative approach is used in this study by applying panel data regression analysis using secondary data available from BPS. The research findings identify that GRDP has a positive and significant impact on labor absorption in Indonesia. Education level also has a significant positive impact, while the health variable identifies an insignificant negative impact on employment. Together, these three variables have a positive and significant impact on labor absorption in Indonesia. Overall, GRDP, education level, and health are able to explain 99.8% of the variation in labor absorption in Indonesia during the period 2017-2023.